2015
DOI: 10.1021/acs.est.5b03383
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intrinsic Colloid Formation on Migration of Cerium through Fractured Carbonate Rock

Abstract: Migration of colloids may facilitate the transport of radionuclides leaked from near surface waste sites and geological repositories. Intrinsic colloids are favorably formed by precipitation with carbonates in bicarbonate-rich environments, and their migration may be enhanced through fractured bedrock. The mobility of Ce(III) as an intrinsic colloid was studied in an artificial rainwater solution through a natural discrete chalk fracture. The results indicate that at variable injection concentrations (between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 62 publications
(131 reference statements)
1
14
0
Order By: Relevance
“…In the tracer solution prior to injection, most of the Ce (93 ± 0.5%), some of the Sr (34 ± 4%), and very little of the Cs and Re (6.0 ± 3 and 1.3 ± 9%, respectively) were associated with the particulate fraction ( Table S3 ). In the presence of carbonates, Ce readily precipitates out of the solution as Ce 2 (CO 3 ) 3 ·8H 2 O, 11 and these have been shown to heteroaggregate with bentonite. 27 Similar bentonite–Ce heteroparticles were measured using dynamic light scattering in a filtered groundwater pumped from the same location as the present experiment, and sizes were found to range from 2.9 to 3.5 μm.…”
Section: Resultsmentioning
confidence: 99%
“…In the tracer solution prior to injection, most of the Ce (93 ± 0.5%), some of the Sr (34 ± 4%), and very little of the Cs and Re (6.0 ± 3 and 1.3 ± 9%, respectively) were associated with the particulate fraction ( Table S3 ). In the presence of carbonates, Ce readily precipitates out of the solution as Ce 2 (CO 3 ) 3 ·8H 2 O, 11 and these have been shown to heteroaggregate with bentonite. 27 Similar bentonite–Ce heteroparticles were measured using dynamic light scattering in a filtered groundwater pumped from the same location as the present experiment, and sizes were found to range from 2.9 to 3.5 μm.…”
Section: Resultsmentioning
confidence: 99%
“…However, colloids can be remobilised in case of heavy rain and the impact of varying flow rates should be investigated. In summary, while Tran et al (2015) demonstrated that inorganic cerium colloids are not particularly mobile in a carbonated fractured rock, Tran et al (2016) found that cerium mobility can be significant owing to organic mineral colloid associations (see the section Colloid-facilitated transport) in the same carbonated fractured rock.…”
Section: Sorption Processesmentioning
confidence: 98%
“…Cerium has been studied because of its analogy to trivalent actinides. Tran et al (2015Tran et al ( , 2016 investigated the transport of cerium in fractured carbonate rocks, focusing mostly on how the intrinsic formation of cerium carbonate colloids, and the presence of humic acid and bentonite, can affect cerium mobility (the influence of carbonates is discussed in Sorption processes). Tran et al (2016) used a chalk core to study the impact of bentonite and humic acid on the transport of cerium.…”
Section: Rare Earth Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tran 9 investigated the geological migration of Ce in fractured carbonate rock formations and found that in a groundwater environment with pH 7-9, the main rare-earth carbonate complex ions are RECO 3 + and RE(CO 3 ) 2…”
Section: Introductionmentioning
confidence: 99%